Occupational therapy's role in hospice care: promoting participation at the end-of-life - Hahn, Ellie, author; Swink, Laura, mentor (Colorado State University. Libraries, 2025)
This capstone project aims to improve understanding, implementation, and advocacy regarding occupational therapy's (OT) scope of practice in hospice care through the development of targeted educational programs for entry-level OT students and practicing clinicians. Completed as part of Colorado State University's occupational therapy program, the project addresses critical barriers to OT's inclusion in end-of-life care—namely, limited education for OT professionals and insufficient interprofessional awareness of OT's distinct contribution as a member of the hospice team. Outcomes of the project include a guest lecture slide deck, an advocacy handbook, a curated resource list, and survey instruments, all aimed at reinforcing OTs value in promoting quality of life, comfort, and meaningful occupational participation at the end-of-life. These materials were trialed with 110 participants across academic and professional development settings. Data collected through pre- and post-surveys indicate significant increases in self-rated proficiency surrounding OT's role in end-of-life care, as well as improved confidence in advocating for OT services. Qualitative feedback further supports these findings and reflects insight into OT's contributions to hospice care. The project also established sustainable partnerships with mentors and professional organizations to promote long-term dissemination and impact. Anticipated outcomes include increased OT presence on hospice teams, enhanced client outcomes related to occupational engagement and wellbeing, and broader interprofessional and intraprofessional recognition of OT's value. This capstone provides an educational and advocacy model to support the integration of OT into end-of-life care.
Colorado State University Occupational Therapy Doctoral Capstone project.
Keywords: occupational therapy; end-of-life; hospice; quality of life